RANCANG BANGUN TIMBANGAN BERAT DAN TINGGI BADAN IDEAL BERDASARKAN METODE BROCHA DENGAN KELUARAN SUARA BERBASIS ARDUINO MEGA 2560 - Kusnadi, Kusnadi; Sari, Hikmah Maya; Rizkiansyah, Rakhmad; Putri, Elysa Aziza (Politeknik Unggulan Kalimantan, 2024)
The measurement of a patient's weight and height is of great importance in the context of medical examinations, as it allows for the early detection of diseases. However, it is important to note that many individuals do not have an ideal body weight, with some being overweight and others underweight. Being overweight can lead to obesity, while being underweight is often associated with malnutrition. Therefore, the objective of this research is to develop a weight and height scale based on the Broch method with accurate output and printable results. The research methodology employed is research and development (R&D). The methodology employed in this research comprises preliminary research, product design, design review, design revision, product testing, and validation. Based on the results of the product testing, the following conclusions can be drawn: the adapter output voltage measurement is 12.13 VDC, with an error of 0.13 VDC and an error of 1.1%. The average voltage measured during testing of the Arduino Mega 2560 was 5.01 VDC, with an error of 0.01 VDC and an error of 0.2%. Ultrasonic sensor readings at a distance of 185 cm demonstrated no error (0 cm), with an error of 0%. Load cell readings at a distance of 40 kg exhibited an error of 0.67 kg and an error of 1.6%. The validation assessment received a rating of 100% from material experts and 96% from media experts. Referring to the feasibility category table, the result is designated as